Phoenician Bathing in the Hellenistic East: Ashkelon and Beyond - Birney, Kathleen (Bulletin of ASOR, 2017)
Excavations of a Hellenistic neighborhood at Ashkelon revealed a suite of heavily plastered rooms, one with a mosaic floor, decorated in Greek Masonry Style. These rooms resemble the bathing suite identified in an elite 2nd-century residence at Tel Anafa and likely reflect a Phoenician style of "cleansing bathing" documented at Phoenician sites from the 4th through 2nd centuries b.c. Such suites differ in character, bathing type, and placement from Greek public and private baths in the Mediterranean and Levant, as well as from ritual baths in the Judaean tradition. The bathing suites appear at Phoenician and Phoenician-influenced sites in Israel during the Persian and Hellenistic periods but are presently under-recognized. This article presents a set of criteria by which to understand and identify Phoenician bathing suites and argues that the preference for this bathing style may, in part, explain why immersion bathing--popular in the western Mediterranean--failed to catch on in the Hellenistic East until the era of Roman control.